PENGARUH KEAHLIAN KOMITE AUDIT, AUDITOR SPESIALISASI INDUSTRI DAN PENGENDALIAN INTERNAL TERHADAP MANAJEMEN LABA - Parapat, Michael; Mukhlasin, Mukhlasin (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2023)
This research was conducted with the aim of knowing the effect of the Expertise of the Audit Committee, Special Industry Auditors, and Internal Control on Earnings Management in Manufacturing Companies listed on the IDX for the period 2016 – 2018. The independent variables are Audit Committee Expertise, Industry Specific Auditors, and Internal Control and the dependent variable is Earnings Management. The data analysis method uses linear regression analysis using the IBM SPSS Statistics 25 program. The data used is taken from secondary data originating from annual reports and financial reports with a sample selection procedure using a purposive sampling method with a total sample of 207 observational data consisting of 69 companies. Data analysis used is descriptive statistical analysis, classic assumption test, compatibility test, and hypothesis testing. The results of this study reveal that the expertise of the Audit Committee and Industry Specific Auditors has no effect on Earnings Management and Internal Control has an impact on Earnings Management.